2014
DOI: 10.1586/1744666x.2014.943664
|View full text |Cite
|
Sign up to set email alerts
|

Fecal volatile organic compounds: a novel, cheaper method of diagnosing inflammatory bowel disease?

Abstract: The investigation of a novel, cheaper method of diagnosing inflammatory bowel disease (IBD) is an area of active research. Recently, investigations into the metabolomic profile of IBD patients and animal models of colitis compared to healthy controls has begun to receive considerable attention and correlations between the fecal volatile organic compound (VOC) metabolome and IBD is merging. Patients and clinicians have often reported a change in odor of feces during relapse of IBD. Therefore, this article will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The gut microbiome is critical in maintaining mucosal homeostasis and it is altered in IBD compared with healthy controls, showing reduced diversity. 36 , 37 The VOCs of fecal matter are distinct in IBD compared with healthy controls 38 supporting this link. Walton et al 39 demonstrated that several VOCs in the headspace of feces differ markedly between patients with CD and other gastrointestinal conditions including UC and irritable bowel syndrome.…”
Section: Discussionmentioning
confidence: 89%
“…The gut microbiome is critical in maintaining mucosal homeostasis and it is altered in IBD compared with healthy controls, showing reduced diversity. 36 , 37 The VOCs of fecal matter are distinct in IBD compared with healthy controls 38 supporting this link. Walton et al 39 demonstrated that several VOCs in the headspace of feces differ markedly between patients with CD and other gastrointestinal conditions including UC and irritable bowel syndrome.…”
Section: Discussionmentioning
confidence: 89%
“… 3 − 11 Various studies have demonstrated the diagnostic potential of VOCs in both pediatric and adult IBD populations by analyzing VOCs deriving from urine, exhaled breath, and feces. 6 , 12 − 14 The majority of studies on fecal VOCs has been performed using gas chromatography/mass spectrometry (GC/MS), allowing for the identification of individual VOCs on a molecular level. This technique is expensive, time consuming, and requires specialized personnel and is therefore not suitable for utilization in a clinical setting.…”
mentioning
confidence: 99%
“…that evaporate or sublimate readily under ambient conditions. They can be captured from a variety of body mediums and have been shown to alter in different disease states [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%